Determinants of Influence Factors of Consumer’s Intention to Use Cashless Transaction Mode Among UTHM students - Ng Peggie; Siti Norziah Ismail (Research in Management of Technology and Business, 2021)
Nowadays, people prefer to use a cashless transaction mode to make a cashless payment. In Malaysia, the government is pushing toward the vision of a cashless society. Digital and cashless society will help to increase economic growth. The objective of this study are to determine the level of awareness of the consumer on cashless transaction mode and identify the influential factors that influences the intention of use cashless transaction mode. The quantitative approach was used to conduct this study. A total of 257 online questionnaires was collected. The respondents are University Tun Hussein Onn Malaysia students. Descriptive analyses, correlation analysis and regression analysis used in this study. The level of awareness of the consumers was high. Perceived usefulness, perceived ease of use, perceived risk, trust as the factors influence the intention to use cashless transaction mode. Perceived usefulness was the influential factor that influences consumer’s intention to use cashless transaction mode. With the limitation of sample size and population, future researcher can investigate bigger population throughout Malaysia.